Strategi Pengembangan Usaha Minuman Sehat Sari Edamame UD. Putra Lanang 27 dengan Penerapan Metode Swot dan Topsis - Ardinata, I Gusti Ngurah Putra; Wiranatha, Agung Suryawan; Satriawan, I Ketut (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2021)
Urban communities are increasingly aware of the need for healthy food and adequate intake of food into the body. One source of food that is practical and healthy is edamame. Edamame is a type of soybean that has a lot of protein and vitamins. One of the home industries that produce edamame extract drinks in Bali is UD. Putra Lanang 27. The high level of competition is one of the determining factors in managing this kind of business in Bali. The aims of this study are: 1) Analyzing internal and external factors that affect UD. Son Lanang 27; 2) Formulating alternative business development strategies at UD. Son Lanang 27; and 3) Choosing a priority strategy for UD's business development. Putra Lanang 27. This study uses SWOT analysis to determine alternative strategies, and TOPSIS method to rank alternative strategies. Suggested strategy to UD. Putra Lanang 27 to grow and develop is market penetration, market development, product development and integration strategy. The priority of the alternative strategy chosen is to expand the market by increasing the number of resellers, and increasing cooperation with supermarkets Keywords: Extract damame drink, Business Development Strategy, SWOT, TOPSIS